Studi Kasus Pasien dengan Diare Rumah Sakit di Kota Makassar - Darmi Arda; Hartaty Hartaty; Hasriani Hasriani (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Diarrhea is the most common cause of death in infants and toddlers. Diarrhea causes poor nutritional status and poor nutritional status and causes growth failure, even permanent weight loss caused by fluid loss and dehydration. The perceived problem is defecation with a soft or liquid consistency, it can even be in the form of water only and the frequency is more often usually three times or more in one day. This case study aims to look at nursing care provided to clients suffering from diarrhea. The research design uses case studies, which aim to describe the nursing care that is carried out. The number of samples 2 people were observed for 3 days in the hospital. The results of observations in the case of patients 1 age 2.5 years with complaints of diarrhea, vomiting and heat with a temperature of 38.3ºC. In the case of 2 patients aged 3 years with complaints of diarrhea and vomiting. Nursing diagnoses in both cases namely diarrhea are associated with intestinal inflammation. Planned interventions are managing diarrhea, monitoring vital signs, managing drug therapy. The implication of this research is to optimize the management of diarrhea in nursing care in Toodler children with acute liquid diarrhea with mild to moderate dehydration.